Grandfather's Christmas camp - McCutcheon, Marc (Clarion Books, 1995)
When Grandfather's three-legged dog Mr. Biggins disappears on Christmas Eve, Lizzie and Grandfather go up the mountain to find him and have an unusual adventure.